Estudio comparativo de dos comités agrícolas de extensión San Ramón, Costa Rica - Campos Sandí, G. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A study was made of the factors affecting the formation and operation of two agricultural committees in San Ramón, Costa Rica, the Committee for Natural Resources and the Committee for the Erradication of the Leaf-eating Ants. Both committees developed as a result of felt needs of the people. Personal characteristics of their members have determined their enrollment in a committee and their participation in activities. The phenomenon of leadership was apparent in both committee. According to the opinion of its members the leaf-eating committee ceased in its operation due to the fact that the main objective had been accomplished; in addition, there was a lack of support in technical services. The Natural Resources committee continued operating because of the enthusiasm of its members, support given by the people and success attained in their different activities